Offshoring, job satisfaction and job insecurity - Santiago Budría; Juliette Milgram Baleix (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
This paper investigates the effects of offshoring on individual job satisfaction and perceived risk of job loss. The authors merge microdata from the German Socio-economic Panel dataset (SOEP) with indicators of insertion in global value chains at the industry level for the period 2000-2013. They test two hypotheses. First, the authors investigate whether workers in industries with higher offshoring intensity report lower job satisfaction and/or are more prone to be unsecure at their jobs. Second, they test whether these effects differ among four categories of collars. Their findings indicate that offshoring is associated with lower job satisfaction. The results are also indicative of some heterogeneity in the offshoring effect, with high skilled white-collar workers being mostly unaffected by offshoring and low skilled blue-collar workers showing the largest negative effects. Discriminating between manufacturing and services activities, the authors find that the extent of heterogeneity and the offshoring effect is relatively larger in manufacturing industries. They also find that the effect of offshoring intensity upon job satisfaction is more negative and significant in periods of economic decline. Finally, the results show that offshoring is not significantly related with job insecurity, a result that applies to all workers' categories. Still, in a period of economic decline job insecurity may increase when the offshoring intensity rises.
Keywords: I31; F6; 330; job satisfaction; job insecurity; offshoring; Germany